The Orthodox Theology In the Post-theological Era - Биговић, Радован (Sabornost - The Theological Year-book, 2013)
Church and Orthodox theology can successfully carry out their missions, considering they examine the signs of the times and interpreting them in the light of the Gospel at any time, if they can offer every generation, in their understandable way, an answer to the eternal human questions about the meaning of the present and future life. It is, therefore, important to learn and understand the world in which we live, its expectations, aspirations and profound and rapid changes that are gradually spreading all over the world. Theology as a prophetic voice and expression of the Church’s self-understanding can only function as a part of antinomy and two-naturalness of the Church’s character. Just as the Church is not of this world, so tends theology to express the experience of grace and transcendent reality which is above and beyond words, terms or names. As the Church lives and goes into the world, so does theology seek a dialogue and communication with the historical present in every age.